Most trumpet moths don’t feed on plants of the nettle family but Paratischeria does: the first discovery of Tischeriidae (Lepidoptera) on Urticaceae in Asia - Stonis, Jonas R.; Diškus, Arūnas; Monro, Alexandre K.; Dai, Xiaohua; Xu, Jiasheng (Zootaxa, 2021)
This is the first record of Urticaceae-feeding trumpet moths (Tischeriidae) from Asia. We describe Paratischeria boehmerica Diškus & Stonis, sp. nov. and P. grossa Diškus & Stonis, sp. nov., two distinctive new species of Tischeriidae recently discovered from Laos, South East Asia, feeding on plants of the nettle family. Urticaceae is a rare host-plant family for leaf-mining Tischeriidae worldwide. The new species are illustrated with photographs of the adults, male and female genitalia, and the leaf mines.